Write dance in the early years: a pre-writing programme for children 3 - 5 - Oussoren, Ragnhild (Thousand Oaks: SAGE Publications, 2020)
'Write Dance books help teachers, parents and learning support assistants teach children to write in a fun an engaging way, through music and song, in ever decreasing movements, from (for example) running round a room, to spraying shaving foam, to writing in sand, to finally picking up a pencil, and drawing shapes and images, before finally constructing letters'--
Keywords: Penmanship -- Study and teaching (Preschool).; Children -- Writing; Motor ability in children; Penmanship, English; Music and dance; Early childhood education -- Activity programs -- United Kingdom